GI Surgery Annual Volume 22 - Sahni, Peush; Pal, Sujoy (GI Surgery Annual,, 2015)
The twenty-second volume of GI Surgery Annual covers a gamut of topics from oesophageal adenocarcinoma, to motility disorders of the colon and rectum, mesenteric tumours as well as the contemporary technique of ALPPS, acute portal vein thrombosis and small for size syndrome in live donor liver transplant. The chapter on advances in gastrointestinal surgery as every year reviews the important new information in the field in an easy to understand manner.